1960
DOI: 10.1149/1.2427537
|View full text |Cite
|
Sign up to set email alerts
|

Particle Growth during Zinc Sulfide Phosphor Preparation

Abstract: The influence of processing conditions, such as time and temperature, and the effect of fluxing agents on the particle size and concomitant properties observed during zinc sulfide phosphor preparation are reported. The particle size increases exponentially with the reciprocal firing temperature and as the square root of the firing time when phosphors are prepared in open boats; the activation energy and frequency constant depend on the flux employed. A particle size anomaly is observed when zinc sulfide powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is interesting to compare the data obtained in the present study with those given by other authors, as reported in Table I in open boats using a flowing helium atmosphere, and measured particle sizes by a gas adsorption method. For ZnS without additives these workers (11) derived an activation energy for particle growth of 28 kcal, 2 together with a time dependence of 0.5. This same value of 30 kcal was quoted by Bube (12) on the basis of a diffusion model.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to compare the data obtained in the present study with those given by other authors, as reported in Table I in open boats using a flowing helium atmosphere, and measured particle sizes by a gas adsorption method. For ZnS without additives these workers (11) derived an activation energy for particle growth of 28 kcal, 2 together with a time dependence of 0.5. This same value of 30 kcal was quoted by Bube (12) on the basis of a diffusion model.…”
Section: Discussionmentioning
confidence: 99%
“…It may be seen that increase of synthesis temperature improves quality of crystal's surface and amount of active surface centers decreases. Above 1100 o C cubic-hexagonal transition in ZnS starts to take place [6] and Sum of q pKa increases again. Further effort was put into the improvement of EL brightness of synthesized phosphors.…”
Section: Surface Properties Of Phosphorsmentioning
confidence: 99%